Dynamics of courage: Personal learning processes in an adapted physical activity- based rehabilitation context, a single case study - Miklos, Mette; Jahnsen, Reidun; Nyquist, Astrid; Hanisch, Halvor (European Journal of Adapted Physical Activity, 2023)
Learning processes require individuals to find the courage to engage in challenging activities. While being highly personal, such processes always occur within a relational social system. Rehabilitation programs with adapted physical activity as the main intervention facilitate opportunities for young adults with the experience of living with a disability to explore their capacities and develop activity competence and agency. This study aims to explore the dynamic relationship between personal experiences and the social processes underpinning a learning process within a rehabilitation program based on adapted physical activity in groups. An ethnographic single case study generated in-depth descriptions illuminating personal experiences, as well as revealed insight into socio-cultural structures and interactional processes. Analysis of the single case demonstrated how the rehabilitation context was experienced as safe. However, the context also included sociocultural expectations guiding attention towards performance demands, limiting the sense of personal agency, and increasing the sense of risk. Trusting collaboration processes were essential in forming support and challenges sensitive to individual needs and sense of risk, and for translating activity experiences into personal learning and activity engagement outside the program context.
Keywords: Learning; ženské pohlaví; odvaha; Rehabilitation; pohybová aktivita; Persons with Disabilities; Motor Activity; Social Interaction; lidé; Female; postižení; učení; Courage; sociální interakce; Young Adult; mladý dospělý; rehabilitace; Humans